Perencanaan Lansekap Wisata Berbasis Edukasi Mangrove di Restoran Akame, Benoa - PRANATHA, I MADE ADI; ARTHANA, I WAYAN; UTAMI, NI WAYAN FEBRIANA (Jurnal Arsitektur Lansekap, 2015)
ABSTRACT Tourism Landscape Planning Based on Education of Mangrove at Akame Restaurant, Benoa   Some regional development in Benoa area utilize mangrove areas. One of them is the development of the Akame Restaurant. This restaurant development greatly affects the existence of mangroves so as to reduce the negative impacts caused by the development of the restaurant then it should be based on regional planning and conservation education to become a sustainable development of the business and tourist area. Planning research method consists of several stages of inventory, analysis, synthesis, concepts and travel planning. Identification and analysis of the potential and constraints of biophysical, economic, social and cultural development in the tourist landscape Akame Restaurant produces spatial concept. The concepts consist of circulation and the concept of infrastructure that supports the activities of the restaurant and the activities of mangrove educational tours. Objects and attraction that are planned include the cultivation of mangrove crabs, bird watching, planting mangrove seedlings, outbound, and canoeing.   Keywords: akame restaurant, landscape planning, landscape tourism, mangrove education